2019
DOI: 10.1177/1478210319878327
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion of refugees into higher education in Norway: A critical analysis of Norwegian higher education and integration policies

Abstract: In numerous countries, the widening participation of underrepresented groups in higher education has become an official part of education policies. However, inequalities continue in some areas, including refugees’ participation. Norway hosts many refugees, but little is known about the social inclusion of refugees into higher education in the country. In this paper, three documents representing Norwegian higher education and integration policies are analysed using an integrated analytical framework constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
(115 reference statements)
1
10
0
1
Order By: Relevance
“…However, some initiatives, such as UiO's outreach to adult education centres, touch on the participation dimension of social inclusion. These practices are in line with trends in the Norwegian higher education and immigration policies documented in a recent study (Abamosa et al, 2020). All this indicates that the universities must do more to be inclusive to refugees.…”
Section: Discussionsupporting
confidence: 83%
“…However, some initiatives, such as UiO's outreach to adult education centres, touch on the participation dimension of social inclusion. These practices are in line with trends in the Norwegian higher education and immigration policies documented in a recent study (Abamosa et al, 2020). All this indicates that the universities must do more to be inclusive to refugees.…”
Section: Discussionsupporting
confidence: 83%
“…The reported data are structured according to the predetermined categories (Table 1): Within the EU context, the studies were performed most of the times in Central European countries (e.g. Germany). The selected studies had different research designs: Seven studies with a qualitative research design; Two studies with a quantitative research design; One study with a mixed method approach. These research instruments were more frequently reported: Five Interviews (Baláž et al, 2021; Bencivenga, 2017; Lambrechts, 2020; Schneider, 2018; Thondhlana, 2020); Three Document analyses (Abamosa et al, 2019; Jungblut et al, 2020; Souto-Outero & Villalba-Garcia, 2015); One literature review (Souto-Outero & & Villalba-Garcia, 2015); Two secondary data analyses (Baláž et al, 2021; Tibajev & Hellgren, 2019); One observation (Bencivenga, 2017). …”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…• The study was published in the last 5 years (2015)(2016)(2017)(2018)(2019)(2020) • Three Document analyses (Abamosa et al, 2019;Jungblut et al, 2020;Souto-Outero & Villalba-Garcia, 2015); • One literature review (Souto-Outero & & Villalba-Garcia, 2015); • Twosecondarydataanalyses(Balážetal.,2021;Tibajev&Hellgren,2019); • One observation (Bencivenga, 2017).…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…Refugee children are the most vulnerable. Schooling can help them overcome stress, avoid negative influences and promote their integration (Abamosa et al, 2020). Teachers and government officials play the key role in the process of integration of refugees (Marcu, 2018;Soriano & Cala, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%